Special report of the director-general on the application of the declaration concerning the policy of apartheid in South Africa (ILO GenevaCH)
Examines recent developments concerning labour and social matters in South Africa and Namibia. Analyzes information supplied by governments, employers' and workers' organizations on action taken against apartheid. Examines international action against apartheid including measures taken by the ILO. Provides information on the continuing implementation of conclusions adopted by the tripartite conference on Apartheid held in Lusaka in May 1984. Includes a summary of actions taken within the framework of the UN and other intergovernmental organizations.
Documentation Centre has : 1983-'88; 1990